2022
DOI: 10.1021/acs.est.1c08875
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorooctane Sulfonamide (PFOSA) Induces Cardiotoxicity via Aryl Hydrocarbon Receptor Activation in Zebrafish

Abstract: Perfluorooctane sulfonamide (PFOSA), a precursor of perfluorooctanesulfonate (PFOS), is widely used during industrial processes, though little is known about its toxicity, particularly to early life stage organisms that are generally sensitive to xenobiotic exposure. Here, following exposure to concentrations of 0.01, 0.1, 1, 10, and 100 μg/L PFOSA, transcriptional, morphological, physiological, and biochemical assays were used to evaluate the potential effects on aquatic organisms. The top Tox functions in ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…35 It has been reported that exogenous compounds, such as tetrachlorodibenzo-p-dioxin (TCDD), stimulated the expression of pro-inflammatory factor iL-1β by activating AhRs in cerebral endothelial cells, which in turn induces BBB damage and development of various neurological diseases. 36 Recently, Chen et al 37 demonstrated that perfluorooctane sulfonamide (PFOSA) induced cardiotoxicity via AhR activation in zebrafish. Although PFPiAs might bind with various proteins, 22 it remains unclear whether they have the potential to activate AhR to induce brain inflammation and neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…35 It has been reported that exogenous compounds, such as tetrachlorodibenzo-p-dioxin (TCDD), stimulated the expression of pro-inflammatory factor iL-1β by activating AhRs in cerebral endothelial cells, which in turn induces BBB damage and development of various neurological diseases. 36 Recently, Chen et al 37 demonstrated that perfluorooctane sulfonamide (PFOSA) induced cardiotoxicity via AhR activation in zebrafish. Although PFPiAs might bind with various proteins, 22 it remains unclear whether they have the potential to activate AhR to induce brain inflammation and neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The ubiquity of PFASs in the environment may threaten the health of aquatic organisms due to the strong bioenrichment and potential toxicity at environmental concentrations. Previous studies have confirmed that the immune system is a sensitive target to PFASs . Perfluorooctanesulfonate (PFOS) and its alternatives, chlorinated polyfluorinated ether sulfonate and sodium p-perfluorous nonenoxybenzene sulfonate, disrupted an antioxidant response and induced anti-inflammatory effects in exposed zebrafish larvae .…”
Section: Introductionmentioning
confidence: 99%
“…The heart is the first functional organ of development in vertebrates such as fish, providing nutrients and oxygen to the brain and systemic systems (Chen et al, 2022). Therefore cardiotoxicity induced by environmental pollutants may disrupt blood circulation and threaten the development of other organs or even life (Ma, Huang, Jiang, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%